Lithium wall conditioning techniques in ADITYA-U tokamak for impurity and fuel control. (2nd December 2021) - Jadeja, K.A.; Ghosh, J.; Yadava, Nandini; Patel, K.M.; Patel, Kiran; Tanna, R.L.; Manchanda, R.; Chowdhuri, M.B.; Raval, J.V.; Nagora, U.C.; Arambhadiya, B.G.; Macwan, Tanmay; et al.
Abstract: In fusion devices, various techniques are employed for coating the plasma facing components (PFCs) including the vessel wall with low-Z material like lithium, boron, and silicon in order to enhance the plasma parameters and control. In ADITYA-Upgrade tokamak, different techniques of lithium wall conditioning are developed and implemented to obtain uniform and sustainable coating of Li on PFCs and the vessel wall. In this paper, two techniques used to generate Li from the source are reported. In one of the technique, a heated (fixed temperature of ∼120 °C) Li-rod is placed inside the hydrogen glow discharge cleaning (H-GDC) plasma and the sputtered Li by hydrogen (H) ions and atoms coats the wall and periphery. In the second technique, the Li is vapourized using a high-temperature Li-evaporator and released into the H-GDC plasma for uniform coating of Li on the PFCs and vessel. Significantly enhanced plasma parameters are obtained after Li coating by both techniques, with the evaporated Li performed better than the Li rod case. With the Li coating obtained with evaporated Li at 600 °C (550 mg Li) with H-GDC, the Li wall conditioning has been observed to be sustaining for in a larger number of plasma discharges in comparison to non-H-GDC assisted Li deposition. As the melting temperature of lithium hydride (LiH) is much higher (688.7 °C) than that of lithium (180.5 °C), this enhance the longer Li-coating lifetime relatively due to the formation of Li–H molecules on the vessel wall and PFCs. In ADITYA-U the carbon impurity and hydrogen recycling, due to relatively high surface area of graphite PFCs as well as their proximity to the plasma, limits the plasma performance and effective controls. Hence, H-GDC, H-GDC with Li-rod sputtering or Li evaporation, helium-GDC, argon–hydrogen mixtures-GDC in particular sequence are carried out to obtain better plasma discharges. The Li coating techniques and their effect on tokamak plasma discharges of ADITYA-U are discussed in this paper.